2010
DOI: 10.1074/jbc.m110.126870
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Membrane Phospholipid Unsaturation Induces Unfolded Protein Response

Abstract: Various kinds of fatty acids are distributed in membrane phospholipids in mammalian cells and tissues. The degree of fatty acid unsaturation in membrane phospholipids affects many membrane-associated functions and can be influenced by diet and by altered activities of lipid-metabolizing enzymes such as fatty acid desaturases. However, little is known about how mammalian cells respond to changes in phospholipid fatty acid composition. In this study we showed that stearoyl-CoA desaturase 1 (SCD1) knockdown incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
214
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(232 citation statements)
references
References 51 publications
16
214
1
1
Order By: Relevance
“…PERK is also activated by membrane lipid saturation (10,19). To test if luminal-independent signals are involved in that process too, an ER-targeted PERK lacking its luminal stresssensing domain (ΔLD-PERK, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PERK is also activated by membrane lipid saturation (10,19). To test if luminal-independent signals are involved in that process too, an ER-targeted PERK lacking its luminal stresssensing domain (ΔLD-PERK, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Increased membrane lipid saturation by genetic or pharmacological inhibition of stearoyl CoA desaturase 1 (SCD1) (19) and by loading of cultured cells with the saturated fatty acid palmitate (10) has been reported to promote UPR signaling. In keeping with these observations, exposure to an SCD1 inhibitor resulted in a fourfold increase in Xbp1 mRNA splicing in FL-IRE1α-expressing cells, which increased to eightfold when compounded with palmitate loading.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that insufficient desaturase activity (SCD1 knockdown) or decreased incorporation of unsaturated fatty acids in membrane phospholipids (LPCAT3 knockdown) can synergistically induce the UPR. The effect is likely due to a decrease in membrane phospholipids unsaturation as it is further enhanced by saturated while it is rescued by unsaturated fatty acids [69] ( Figure 2B). Recent findings suggest that ER lipid perturbation can trigger the UPR directly and independently of luminal accumulation of unfolded proteins.…”
Section: Lipotoxic Er Stressmentioning
confidence: 99%
“…calcium storage and membrane lipid composition. [4][5][6][7][8][9][10][11] For example, decreased synthesis of phosphatidylcholine (PC), altered fatty acid desaturation, abnormal sterol levels, and organismal obesity all induce the UPR ER . …”
Section: Introductionmentioning
confidence: 99%